The river swimmer : novellas - Harrison, Jim, 1937-2016 (Grove Press, 2013)
Two novellas provide insight into the human condition as a sixty-year-old art history academic embarks on an unexpected journey of discovery and a young farm boy is drawn to the water of Lake Michigan as an escape.